Early calf slaughter: impact of industry-led policy interventions on trends in Ireland, 2024 - Oakes, Sinnead; Ryan, Eoin; Byrne, Andrew W. (Frontiers in Veterinary Science, 2025)
The dairy industry produces a surplus of male calves with low monetary value and slaughtering them at a young age has been used as a means of disposal, raising ethical concerns. In 2024, changes to the dairy industry quality assurance standards were introduced to prevent this practice in Ireland. The objectives of the present study were to explore trends in calf slaughter, measure the effects of the intervention, and to identify any unintended consequences of the industry-led policy. The data on 16,598 <56-day-old calves slaughtered from a total of 1,937,533 born, January to May 2024, were obtained from national databases. We fitted negative binomial regression models to the count of slaughtered calves per birth herd to assess associated contributory factors. The study revealed that there has been a drop in early calf slaughter from an average of 1.09% of calves in 2018–2022 to 0.86% in 2024. There were 1,241 birth herds of slaughtered calves but only 247 herds presented calves for slaughter. Furthermore, 1,019 of the birth herds moved calves to a presenting herd before slaughter. The birth herds were mostly members of the dairy industry quality assurance scheme (97%). The presenting herds had lower membership (83%) and tended to send larger number of calves. One single presenting herd accounted for 20% of the total slaughtered calves. These results show that the intervention had a sizable effect in its first year and highlights the potential for industry-driven policy changes to influence the choices farmers make, and the need for continual monitoring.